FAKTOR EKSPLOITASI HUTAN DI SUB REGION KALIMANTAN TIMUR - Soenarno; Wesman Edom; Zakaria Basari; Dulsalam; Sona Suhartana; Yuniawati (BRIN Publishing, 2016)
Forest harvest is the first activity to undertake in extracting logs from the forest site. The amount of wood wastes generated during logging operation can be used for measuring the value of exploitation factor (FE). The greater FE indicates more efficient of wood utilization. Indonesian government has so far decided the formal FE is 0.7. This value is no longer accurate for the current better forest management situation which adopting practices of reduced impact logging-RIL and or RIL-C. Considering from economic aspects, the FE value has a very important role, i.e. as multiplying factor in determining annual allocation of wood production (JPT) and as a basic parameter in predicting earn business provision of natural forest (PSDH). Ecological aspects may interprete that the bigger FE value will bring about reduction of forest damages. This paper examines the FE in Sub-Region of East Kalimantan. Results show that the proper FE value for the East Kalimantan Province is ranged between 0.77 – 0.89. The amount of FE value is more influenced by factor of feller skills than the management competence factor of IUPHHKHA.